BENTUK KOREOGRAFI MEUDIKEE ANGGOK DI DAYAH DARUL HUDA DESA BAYI KECAMATAN TANAH LUAS LHOKSUKON KABUPATEN ACEH UTARA - Ovi Wulandary; Rhd Nugrahaningsih; Sitti Rahmah (Gesture: Jurnal Seni Tari, 2018)
Abstract − This study discusses the form of choreography meudikee anggok in dayah Darul Huda Bayi Village District Lhoksukon Land Area North Aceh District. Aims to describe the form of choreography meudikee Anggok in one studayah District of North Aceh.The theory used in this research is the theory of Choreography Sal Murgiyanto that choreography is the process of selecting and arranging movements into a dance, in which there is a creative behavior. Composition is part or aspect of creative behavior. The time spent in the study for two months, starting from July to September. The location of this research was conducted in Bayi Village, Tanah Luas Lhoksukon Sub District, North Aceh District. The population in this study are the dayah-dayah (pengajian) in the District Land Luas Lhoksukon District of North Aceh and the sample is Dayah Darul Huda Bayi Village. The research analysis used is descriptive qualitative. Technique of collecting data is done by observation, interview, documentation and literature study. The result of the research based on the data obtained shows that the form of Meudikee Anggok choreography is a form of the dance result from the elements of dance composition that is, motion meudikee Anggok is the motion of dhikr distortion and distillation, has some motive motive and dihat from energy aspect space and time. The design of the floor created is a straight line. The top designs created are pure, flat, curved, painted, contrasting, medium, deep and straight design. The music design follows the rhythm of chanting dhikir in khairat that brought the radat. The dramatic design created by multiple cone. Dynamics according to the chanting dhikrdhikr in khairat that brought the radat. The composition of the group that created the composition of a large group. The theme is Prophet Muhammad SAW. Makeup everyday. Muslim clothing namely peci, koko shirt and sarong. Not using property. The stage or stage stage is open. Tata the light from the sun. Keywords: Choreography Shape, Meu Dike Anggok, Dayah, Bid'ah, Dalail